2009
DOI: 10.1177/1352458509355461
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion tensor imaging abnormalities in depressed multiple sclerosis patients

Abstract: Depression is common in patients with multiple sclerosis, but to date no studies have explored diffusion tensor imaging indices associated with mood change. This study aimed to determine cerebral correlates of depression in multiple sclerosis patients using diffusion tensor imaging. Sixty-two subjects with multiple sclerosis were assessed for depression with the Beck Depression Inventory (BDI-II). All subjects underwent magnetic resonance imaging. Whole brain and regional volumes were calculated for lesions (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
80
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 33 publications
(33 reference statements)
5
80
1
Order By: Relevance
“…In MS patients, not only psychological, somatic or social implications of MS contribute to depression [1] and SD [23], but also MS-specific lesions, for example, in projection areas of the basal limbic system [37] give rise to depressive symptoms such as anhedonia or depressed affect [1,[37][38][39]. In 109 women with MS, Gold et al [38] found associations between depression and reduced thickness of the right hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…In MS patients, not only psychological, somatic or social implications of MS contribute to depression [1] and SD [23], but also MS-specific lesions, for example, in projection areas of the basal limbic system [37] give rise to depressive symptoms such as anhedonia or depressed affect [1,[37][38][39]. In 109 women with MS, Gold et al [38] found associations between depression and reduced thickness of the right hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…31 Individual differences in depression in MS patients have been associated with altered regional activity and functional connectivity patterns within the limbic system.…”
mentioning
confidence: 99%
“…24,29,31,33 This is supported by the results of a comparative study in which depressed MS patients exhibited significantly more frontal lobe pathologies than nondepressed ones. 48 In fact, frontal lobe lesions could result in inappropriate behavior, lack of empathy, abnormal affect, and executive/cognitive dysfunction, which could be the presenting psychiatric symptoms of MS. 26,49 Temporal lobe pathologies, particularly on the left side, were found to be associated with the occurrence of psychosis in MS. 9,27 Notably, the role of temporal lobe lesions in psychiatric manifestations was further highlighted in studies comparing MS groups with or without psychiatric symptoms. 35,50 New cerebellar and brainstem lesions have been documented in one patient presenting with catatonia.…”
Section: Radiological Hints Toward the Diagnosis Of Psychiatric-onset Msmentioning
confidence: 99%